OPTIMALISASI PEMUNGUTAN PAJAK BUMI DAN BANGUNAN PEDESAAN DAN PERKOTAAN OLEH UPTD DINAS PENDAPATAN DAERAH KECAMATAN MANDAU KABUPATEN BENGKALIS - Dewi Amelia; Harapan Tua R.F.S (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Implementation of Land and Building Tax Collection Rural and Urban have not yet reached the target and still less than optimal. This is because no accumulation of sources of property tax revenues by officers, still encountered taxpayers who do not comply with the obligation to pay taxes, a lack of socialization of property tax to rural and urban communities. Based on the researchers conducted research on Optimization of Land and Building Tax Collection Rural and Urban By UPTD Revenue Service Mandau sub Bengkalis. The problem in this research is How Optimization of Land and Building Tax Collection in District Mandau Bengkalis and any factors that inhibit Optimization of Land and Building Tax Collection in the District of Mandau Bengkalis. The study used the theory of optimization models Marihot Pahala Siahaan. This research method used is descriptive method of qualitative data collection techniques by observation and interviews in which the parties involved in the optimization of the collection as an informant. Research results Optimizing Collection of Tax on Land and Building Rural and Urban by UPTD Department of Revenue Mandau sub Bengkalis in the category less than the maximum it is due to the persistence of tax payers who are not registered as well as subject and object property tax rural and urban areas that should be recorded but in fact has not been recorded by the Regional Income UPTD in the process of making payment of taxpayer confusion and resulted in the payment is not made on time. The factors that can inhibit namely internal factors: lack of firmness or sanctions laws regarding taxation, lack of socialization and lack of human resources. External factors: lack of knowledge about the importance of tax payers taxes, and taxpayers are not enthusiastic in terms of tax payments. Keywords: Optimization, Harvesting, Land and Building Tax Rural and Urban Areas.